2016
DOI: 10.1177/0046958016667596
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Race/Ethnicity and Socioeconomic Status on Risk-Adjusted Readmission Rates

Abstract: Under the Hospital Readmissions Reduction Program (HRRP) of the Centers for Medicare & Medicaid Services (CMS), hospitals with excess readmissions for select conditions and procedures are penalized. However, readmission rates are not risk adjusted for socioeconomic status (SES) or race/ethnicity. We examined how adding SES and race/ethnicity to the CMS risk-adjustment algorithm would affect hospitals’ excess readmission ratios and potential penalties under the HRRP. For each HRRP measure, we compared excess re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…However, equivalent discourse over the quality of data available for SES adjustment has been lacking. To date, there have been no fewer than 8 studies 28,29,30,31,32,33,34,35 that have attempted to contrast hospital readmission rates against socioeconomic data derived from the ACS. However, to our knowledge, no study has attempted to disentangle its findings from the reliability of the estimates.…”
Section: Discussionmentioning
confidence: 99%
“…However, equivalent discourse over the quality of data available for SES adjustment has been lacking. To date, there have been no fewer than 8 studies 28,29,30,31,32,33,34,35 that have attempted to contrast hospital readmission rates against socioeconomic data derived from the ACS. However, to our knowledge, no study has attempted to disentangle its findings from the reliability of the estimates.…”
Section: Discussionmentioning
confidence: 99%
“…At the hospital level, previous research has consistently indicated hospitals serving minority populations experience higher readmissions for HF, AMI, PN, and diabetes [14,15]. County characteristics that correlate highly with readmission rates include minority and vulnerable populations, socioeconomic status (negative correlation), educational level (negative correlation), high unemployment rate, a large number of individuals who never married, and a high percentage of Medicare recipients per 100,000 residents [15][16][17]. At the individual level, Martsolf et al (2016) reported race, ethnicity, and low socioeconomic status affect hospitals' excess readmission ratios and significantly impact hospitals' risk for penalties.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have explored the impact of county [12,17], hospital [13,21], and patient characteristics [2,8]individually on hospitals' performance on 30-day readmission for congestive HF, AMI, and PN. However, to our knowledge, no study has explored the impact of community diversity in a hospital referral region (HRR) as it relates to its demographics and racial/ethnic makeup, on a hospital's 30-day readmission rate.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in health care delivery based on local and regional factors, items beyond patient or provider control, are also topics that have been highlighted over the last several years ( Bernheim et al, 2016 ; Kshirsagar et al, 2017 ; Manickam et al, 2017 ; Martsolf et al, 2016a ; Martsolf et al, 2016b ). For example, regional differences have been associated with outcomes in the ESRD setting, particularly when the West coast is compared against other regions of the US ( Almachraki et al, 2016 ; Kshirsagar et al, 2017 ; Mu et al, 2018 ), despite near universal care and coverage offered in the US for ESRD.…”
Section: Introductionmentioning
confidence: 99%